Green Fabrication of Silver Nanoparticles by Gum Tragacanth (Astragalus gummifer): A Dual Functional Reductant and Stabilizer. (14th June 2012) - Kora, Aruna Jyothi; Arunachalam, Jayaraman
Abstract : A simple and ecofriendly procedure have been devised for the green synthesis of silver nanoparticles using the aqueous extract of gum tragacanth ( Astragalus gummifer ), a renewable, nontoxic natural phyto-exudate. The water soluble components in the gum act as reductants and stabilizers. The generated nanoparticles were analyzed using UV-visible spectroscopy, transmission electron microscopy, X-ray diffraction, Fourier transform-infrared spectroscopy, and Raman spectroscopy. The role of gum concentration and reaction time on the synthesis of nanoparticles was studied. By regulating the reaction conditions, spherical nanoparticles of 13.1 ± 1.0  nm size were produced. Also, the possible functional groups involved in reduction and capping of nanoparticles has been elucidated. The antibacterial activity of the fabricated nanoparticles was tested on model Gram-negative and Gram-positive bacterial strains with well-diffusion method. These nanoparticles exhibited considerable antibacterial activity on both the Gram classes of bacteria, implying their potential biomedical applications.